Quietly sharing the load? The role of school psychologists in enabling teacher resilience - Beltman, Susan; Mansfield, C.; Harris, A. (Sage Publishers, 2016)
Teacher resilience is associated with positive student outcomes and plays an important role in teacher retention and well-being. School ecologies can enable the resilience of teachers, with prior research illustrating the importance of supportive colleagues, strong leadership, and positive school culture. There is limited research, however, exploring the role of school psychologists in supporting or enabling teacher resilience. Using data from experienced Australian school psychologists and teachers, this exploratory qualitative study examines the role of school psychologists in enabling teacher resilience. Findings show that school psychologists directly and indirectly support teacher resilience, although teachers perceive school psychologists’ main role as work with individual students. Issues pertaining to variations in access and particular roles of school psychologists are discussed. Although further research is needed to clarify and promote the role of school psychologists, this study points to them potentially playing an important role in school ecologies that enable teacher resilience.